Remission after complete excision of an intramedullary hemangioma with an identifiable tumor plane in a dog. Issue 8 (9th June 2019) - Yanke, Amy B.; Miller, Margaret A.; Fulkerson, Caroline V.; Bohn, Kendra; Bentley, R. Timothy
Abstract: Objective: To describe the use of an identifiable tumor plane (ITP) during myelotomy to excise an intramedullary hemangioma in a dog and report the outcome. Study design: Case report. Animals: One 5.5‐year‐old 42.9‐kg spayed female Leonberger dog. Methods: Clinical signs included progressive proprioceptive deficits of both pelvic limbs. Magnetic resonance imaging was consistent with a dorsal intramedullary mass at L3‐L4. A laminectomy of the third and fourth lumbar vertebrae provided access for dorsal myelotomy. A clear surgical ITP was identified between the intramedullary mass and the spinal cord facilitating complete surgical resection. Results: Histopathological examination was consistent with a hemangioma. Postoperative MRI was consistent with complete excision of the mass. No evidence of recurrence was found by MRI at 3 months and at 22 months after surgery. Mild proprioceptive deficits persisted in the right pelvic limb. Conclusion: A clear ITP was present, and gross‐total resection (GTR) was achieved without significant morbidity. Persistent clinical remission resulted from surgery as the sole therapy. Clinical significance: For an intramedullary tumor, GTR is the absence of visible tumor on intraoperative inspection combined with the absence of intramedullary contrast enhancement on postoperative MRI. When an ITP is present, GTR and resultant long‐term remission may be more likely.